Thermo‐Hydro‐Chemical Simulation of Mid‐Ocean Ridge Hydrothermal Systems: Static 2D Models and Effects of Paleo‐Seawater Chemistry. (8th December 2022) - DePaolo, Donald J.; Sonnenthal, Eric L.; Pester, Nicholas J.
Abstract: Decades of research have resulted in characterization of the ocean floor manifestations of mid‐ocean ridge (MOR) hydrothermal systems, yet numerical models accounting for the connections between heat transfer, hydrology and geochemistry have been slow to develop. The Thermo‐hydro‐chemical code ToughReact can be used to describe the coupled effects of fluid flow, heat transfer, and fluid‐rock chemical interactions that occur in MOR systems. We describe the results of 2‐dimensional simulations of steady state flow in fractured diabase with mineral‐fluid chemical reactions. Basal heating and specified permeability yield maximum temperature of 400°C. Total fluid flux and high fracture flow velocities are in accord with observations. Fluid chemistry, mineralogical changes and 87 Sr/ 86 Sr ratios can be compared to observations to assess and calibrate models. Simulated high temperature fracture fluids have Mg and SO4 near zero, elevated Ca and 87 Sr/ 86 Sr of about 0.7040. Total alteration is 10%–50% for simple models of spreading. Anhydrite forms mainly near the base of the upwelling zone and results in substantial local fracture porosity reduction. A calibrated model is used to predict how Sr isotopes and other features of altered oceanic crust would be different in the Cretaceous (95 Ma) early Proterozoic (1, 800 Ma) and Archean (3, 800 Ma), when seawater may have had high Ca and Sr concentrations, lower pH, higher temperature, and lower Na, Mg, and SO4 . The simulations are offered as a start on what ultimately may require a longer‐term community effort to better understand the role of MOR thermo‐hydro‐chemical systems in Earth evolution. Plain Language Summary: This paper describes the results of a numerical simulation of the thermal, hydrological, and chemical processes that occur in a simplified mid‐ocean ridge (MOR) hydrothermal system. The simulations exhibit the relationships between fluid flow, temperature, heat transfer, and mineral‐fluid reactions. A simplified rock composition is used corresponding to diabase. The model accounts for flow mainly in fractures, and can reproduce many of the key aspects of seafloor vent fluid chemistry and the altered rocks found in ophiolites. Sr isotopes are also tracked. There are several key issues that must be addressed in constructing such models, and many of these are described in detail. The model parameters are calibrated against modern seafloor hydrothermal systems and then used to predict how the geochemical processes, including Sr isotope exchange, would be affected by changing seawater chemical composition, as is likely to be the case for Cretaceous, Paleozoic and Precambrian oceans. The simulations presented are viewed as a first step in building a more complete simulation capability for MOR hydrothermal systems to better understand their role in Earth evolution. Key Points: Mid‐ocean ridge hydrothermal systems, a key component of global geochemical cycles, involve coupled heat transfer, fluid flow, and chemical reactions The thermo‐hydro‐chemical code ToughReact has the capabilities to simulate the coupled processes and improve understanding of these critical global systems We use the model to assess effects of different seawater chemistry in the Cretaceous and Precambrian, which include large differences in Sr isotope and Na exchange